ANALISIS PENGARUH ZAKAT, INFAK, DAN SEDEKAH (ZIS), INFLASI, DAN PERTUMBUHAN EKONOMI TERHADAP KETIMPANGAN PENDAPATAN DAN KEMISKINAN DI INDONESIA - Amani Amani; M. Shabri Abd. Majid (Fakultas Ekonomi dan Bisnis UNSYIAH, 2022)
AbstractThis study aimed to examine and analyze the effect of ZIS, inflation, and economic growth on income inequality and poverty in Indonesia. This type of research was in the form of quantitative research and the data used was secondary data in the form of monthly data in the 2012-2020 period. The research data were accessed through the website of the Indonesian Central Statistics Agency and the Information Management and Documentation Officer of the Indonesian National Amil Zakat Agency. The results of the analysis of the study showed that ZIS and inflation had a negative and significant effect on income inequality and poverty. Meanwhile,economic growth had a positive and significant impact on income inequality. However, economic growth had a negative and insignificant effect on poverty. The results of this study also showed the importance of optimizing the collection and management of ZIS in reducing income inequality and poverty in Indonesia. In addition, the efforts to stabilize prices through monetary policy played an important role in reducing inequality and poverty.Keywords: Income Inequality, Poverty, ZIS, Inflation, Economy Growth.